Resource-aware policies. (February 2017) - Bottoni, Paolo; Fish, Andrew; Heußner, Alexander; Presicce, Francesco Parisi
Abstract: In previous papers, we proposed an extension of Spider Diagrams to object-oriented modelling, called Modelling Spider Diagrams (MSDs), as a visual notation for specifying admissible states of instances of types, and for verifying the conformance of configurations of instances with such specifications. Based on this formalisation, we developed a notion of transformation of MSDs, modelling admissible evolutions of configurations. In the original version of MSD, individual instances evolve independently, but in reality evolutions often occur in the context of available resources, so transformations must be extended to take this into account. In this paper we provide an abstract syntax for MSDs, in terms of typed attributed graphs, and a semantics for the specification of policies based on notions from the theory of graph transformations, and we associate with them a notion of resources. We also introduce a synchronisation mechanism, based on annotation of instances with resources, so that the transformations required by a policy occur with respect to available resources. In particular, resources can be atomically produced or consumed or can change their state consistently with the evolution of the spiders subject to the policy. Highlights: Formal graph-transformation abstract syntax for extending Spider Diagrams to object-oriented modelling. Consequent formalisation of the notion of policy and of story conforming to a policy. Formal treatment of the dependence of policies on resources. Construction for synchronising the concurrent evolution of elements conforming to a policy with the resources involved.